An Egyptian Medical Officer and Qurʾān Commentator in Ottoman Syria: Muḥammad b. Aḥmad al-Iskandarānī and His Tafāsīr in the 19th Century - Daneshgar, Majid (Oriente moderno, 2021)
Abstract This article pays a particular attention to an Arab army physician and scholar from the mid-19th century who placed empirical science at the center of Islamic thought and situated it within Qurʾānic exegetical debates. He is the Egyptian Muḥammad ibn Aḥmad al-Iskandarānī, a medical officer who ended up working in Ottoman Syria, and whose works were copied and printed (in)directly by the Ottomans. Apart from the limited information contained in previous scholarly literature, which, on the basis of his first commentary alone, repeatedly presents this commentator as one of the first people to have produced a “scientific interpretation of the Qurʾān”, little is known about his personal and professional background and the production of his commentaries. This study also sheds light on exegetical and intellectual directions produced outside Egypt in the 19th century.